Quantitative Measurement of Varicella-Zoster Virus Infection by Semiautomated Flow Cytometry - Gates, Irina V. (American Society for Microbiology (ASM), 2009)
Varicella-zoster virus (VZV; human herpesvirus 3) is the etiological cause of chickenpox and, upon reactivation from latency, zoster. Currently, vaccines are available to prevent both diseases effectively. A critical requirement for the manufacturing of safe and potent vaccines is the measurement of the biological activity to ensure proper dosing and efficacy, while minimizing potentially harmful secondary effects induced by immunization. In the case of live virus-containing vaccines, such as VZV-containing vaccines, biological activity is determined using an infectivity assay in a susceptible cellular host in vitro. Infectivity measurements generally rely on the enumeration of plaques by visual inspection of an infected cell monolayer. These plaque assays are generally very tedious and labor intensive and have modest throughput and high associated variability. In this study, we have developed a flow cytometry assay to measure the infectivity of the attenuated vaccine strain (vOka/Merck) of VZV in MRC-5 cells with improved throughput. The assay is performed in 96-well tissue culture microtiter plates and is based on the detection and quantification of infected cells expressing VZV glycoproteins on their surfaces. Multiple assay parameters have been investigated, including specificity, limit of detection, limit of quantification, range of linear response, signal-to-noise ratio, and precision. This novel assay appears to be in good concordance with the classical plaque assay results and therefore provides a viable, higher-throughput alternative to the plaque assay.